Peran Brand Awareness Memediasi Pengaruh Viral Marketing terhadap Purchase Intention Produk Avoskin Beauty (Studi Pada Pengguna Aplikasi TikTok di Kota Denpasar) - Ni Putu Diah Sukma Yanti; Ni Made Purnami (Universitas Triatma Mulya, 2024)
Viral marketing is important for companies to implement because considering that currently TikTok social media users are increasing, businesses need to aggressively carry out promotions and advertising with the aim of making potential consumers interested they will later buy the products being sold. The aim of this research is to explain the role of brand awareness in mediating the influence of viral marketing on purchase intention for Avoskin Beauty products among TikTok application users in Denpasar City. The number of samples 120 respondents with a purposive sampling method. Data collection was carried out through distributing questionnaires. The collected data was analyzed using path analysis, Sobel test and VAF test. The results of this research show that all hypotheses are accepted. Viral marketing has a positive and significant effect on purchase intention; viral marketing has a positive and significant effect on brand awareness; brand awareness has a positive and significant effect on purchase intention; Brand awareness is a partial mediating variable in the influence of viral marketing on purchase intention for Avoskin Beauty products among TikTok application users in Denpasar City. The implications of this research for the Avoskin Beauty company are expected to increase product excellence, increase product promotion related to product information, and increase brand recognition in the minds of consumers in order to increase consumer purchase intention.